RELEVANSI KOMISI PEMILIHAN UMUM KOTA PEKANBARU DALAM MENINGKATKAN PARTISIPASI POLITIK PEMILIH PEMULA - Ruslyhardy, Ruslyhardy; Harefa, Berianto; Yandra, Alexsander; Sudaryanto, Sudaryanto (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
All stakeholder elements must play an active role in realizing a constructive government. From the highest leadership and without exception to institutions such as the General Election Commission. The problem of low community participation is also a serious problem that occurred in the Pekanbaru city regional elections. According to Myron Weimer, political participation is influenced by several things, as quoted by Mohtar Mas'oed and Collin MacAndrews (2011: 56-57), namely modernization, changes in social class structure, the influence of intellectuals and the increase in modern mass communication, the existence of conflicts between leaders. -political leaders, increasingly broad government involvement in economic, social and cultural elements. Location of the authority by government officials, namely, the Peikanbaru City General Elections Commission. This research is an activity carried out in the form of analysis which involves presenting data systematically and objectively. Based on the results of the results related to the resilience of the Peikanbaru city public election commission in increasing political participation of beginners, it is still not running optimally.Keywords: Relevance, Election, Participation and Politics.